1997
DOI: 10.2307/146181
|View full text |Cite
|
Sign up to set email alerts
|

Why Don't Schools and Teachers Seem to Matter? Assessing the Impact of Unobservables on Educational Productivity

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. University of Wisconsin Press and The Board of Regents of the University of WisconsinSystem are collaborating with JSTOR to digitize, preserve and extend access to The Journal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
179
0
10

Year Published

2001
2001
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 312 publications
(201 citation statements)
references
References 9 publications
6
179
0
10
Order By: Relevance
“…Thus, "which teacher a student happens to get within a school matters more than which school the student happens to attend" (p. 247). Empirical evidence of the impact of teacher effects on student achievement supports previous research concluding that the teacher is the primary school-based determinant who affects the variance in student achievement (Goldhaber & Brewer, 1997;Sanders & Rivers, 1996).…”
Section: Level 5: Student Learning Outcomessupporting
confidence: 60%
“…Thus, "which teacher a student happens to get within a school matters more than which school the student happens to attend" (p. 247). Empirical evidence of the impact of teacher effects on student achievement supports previous research concluding that the teacher is the primary school-based determinant who affects the variance in student achievement (Goldhaber & Brewer, 1997;Sanders & Rivers, 1996).…”
Section: Level 5: Student Learning Outcomessupporting
confidence: 60%
“…Moreover, they found that school characteristics partially reflected the incidence of poverty and the educational level among adults in students' high-school neighborhood. Goldhaber and Brewer (1997) found that family background characteristics had a significant effect on test scores achieved by 18,000 students in the 10th grade, even after controlling for school characteristics and the results of a previously taken math test by the same students. They found that, for instance, years of parental education and family income were positively related to test scores.…”
Section: The Macro Picturementioning
confidence: 89%
“…Oakes, 1985) and different school programs, which apparently favor some or being unfair to others. Also, other approaches investigate teacher-student relationships, for example, how the teacher serves as a model for the student and how he fulfills his educational work according to the expectations and origin of students (Rivkin et al 1998;Goldhaber & Brewer, 1997;Darling-Hammond, 1987;Boe & Gilford, 1992;Mansfield, 2014). No matter how much these approaches ignored class conflicts and social dynamic, they contributed significantly to the study of educational inequality, given that they investigated two extremely important versions of the phenomenon, as the school organization and the teacher-student relationship.…”
Section: Educational Inequality and Social Inequalitymentioning
confidence: 99%